PENGGUNAAN MEDIA PROMOSI FILM ANIMASI DALAM PENINGKATAN PENGETAHUAN TENTANG COVID-19 PADA SISWA/SISWI KELAS II & III SDN 50 BANDA ACEH - Ambia Nurdin; Muhammad Muhammad; Zamzami Zamzami; Bukhari Bukhari; Murtadhahadi Murtadhahadi; Mohd Isa T Ibrahim; Mahyuddin Mahyuddin (Jurnal Dedikasi Pendidikan, 2023)
Covid-19 (corona virus) can infect anyone, but the effect will be more dangerous or even fatal if it attacks the elderly, pregnant women, smokers, sufferers of certain diseases such as asthma, pneumonia, tuberculosis and diabetes mellitus and cancer sufferers. Because this disease is easy to transmit, there is also a high risk of infecting medical personnel who treat Covid-19 patients. In addition, the groups at risk of being exposed to Covid-19 are children, this is because the majority of Covid-19 sufferers are children aged 6-11 years. The purpose of the study was to determine the use of animated film promotion media in increasing knowledge about Covid-19 in class II and III students of SDN 50 Banda Aceh City in 2021. This research method is Correlative Descriptive with Random Sampling technique with a total sample of 71 students. . The time of this research was carried out on October 22-23, 2021. The results showed that of the 71 respondents before giving animated films, most of them had little knowledge about Covid-19 as many as 43 respondents (60.6%), while after giving animated films, most of them Most have good knowledge about Covid-19 as many as 53 respondents (74.6%). The conclusion is that before giving animated films, most of the students have less knowledge, while after giving animated films, most of them have good knowledge. It is hoped that respondents will increase their knowledge about Covid-19and continue to apply health protocols properly.